Drei. Das Triptychon in der Moderne. - Ackermann, Marion; Ullrich, Wolfgang; Valentin, Joachim; Kunstmuseum Stuttgart, Stuttgart (Ostfildern : Hatje Cantz, 2009)
Artschwager, Richard ; Bacon, Francis ; Balla, Giacomo ; Beckley, Bill ; Max, Beckmann ; Coleman, Joe ; Dahlberg, Jonas ; Dix, Otto ; Droese, Felix ; Dubreuil, Pierre et al.
Drei. Das Triptychon in der Moderne, Kunstmuseum Stuttgart, Stuttgart, 7. Februar bis 14. Juni 2009
kunstcatalogus